2010
DOI: 10.1016/j.polymdegradstab.2010.01.024
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of thermal decomposition of poly(ether ether ketone) (PEEK) from a review of decomposition studies

Abstract: A review of the literature on the flammability and decomposition of Poly(oxy-1,4-phenyleneoxy-1,4-phenylenecarbonyl-1,4-phenylene) (PEEK) is presented. This paper provides an overview of the flammability of PEEK and its decomposition mechanisms.Based on this literature, mechanisms have been suggested which attempt to explain the products formed at each stage of PEEK decomposition and indicate the intermediates which should be formed at each of these stages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
158
0
12

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 296 publications
(195 citation statements)
references
References 19 publications
12
158
0
12
Order By: Relevance
“…However it is feasible that it may provide some benefit in high temperature polymers such as polyetheretherketone (PEEK). Studies of the decomposition mechanisms [57] of this polymer show that it does not begin to decompose until 575°C. PEEK's melting point of 343°C makes both aluminium hydroxide and magnesium hydroxide unsuitable.…”
Section: Implications For the Suitability Of Mixtures Of Hydromagnesimentioning
confidence: 99%
“…However it is feasible that it may provide some benefit in high temperature polymers such as polyetheretherketone (PEEK). Studies of the decomposition mechanisms [57] of this polymer show that it does not begin to decompose until 575°C. PEEK's melting point of 343°C makes both aluminium hydroxide and magnesium hydroxide unsuitable.…”
Section: Implications For the Suitability Of Mixtures Of Hydromagnesimentioning
confidence: 99%
“…This result indicates that HT-LS process significantly affects the thermal history of the PEEK material leading to earlier degradation than in the powdered samples. However, signs of decomposition products on PEEK have been reported to appear at 450 °C [42], while colour changes were noticed after exposure for prolonged time at 400 °C [43]. It is therefore not clear whether the EMR D shown in Figure 16 provides a good prediction of the beginning of thermal degradation phenomena in HT-LS, which occurs before the material reaches the highest tensile strength performance available through this manufacturing technique.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…However, cleavage of the carbonyl bond will lead to radical intermediates that are more stable due to resonance effects and would be expected to predominate. In the second decomposition stage, occurs a slower volatilization of the residue, with about 46 to 50% of residue remaining in 900 °C [5,28] . Phase boundary controlled reaction (contracting volume)…”
Section: Nitrogen Atmospherementioning
confidence: 99%
“…Finally, it can be observed that the PEEK left a great amount of residue (~45%).This has also been observed by other authors and has been attributed to the loss of, mainly, phenols as decomposition products, although carbon monoxide (CO) and carbon dioxide (CO 2 ) have also been identified as evolving rapidly over this temperature range possibly as a by-product of the decomposition of PEEK to phenols. This is followed by a slower process of volatilisation of the residue, with over 45% still present even at 1000 °C [5] . Using the Equation 3, the log(β) vesus 1000/T was plotted for the conversion rates of 2.5%, 5.0%, 7.5%, 10%, 12.5% and 15%, and it is showed in Figure 3.…”
Section: Nitrogen Atmospherementioning
confidence: 99%
See 1 more Smart Citation